Effect of Using the Financial Information Technology System (SANAMA: Real-time Monitoring System of the Department of Financial Monitoring and National Treasury) on the Transparency, Accountability, and Audit of the National Budget Statement - Ahmad Barani (Journal of Global Pharma Technology, 2017)
The aim of this study was to investigate the effect of financial information technology system (SANAMA: real-time monitoring system of the Department of Financial Monitoring and National Treasury) on the transparency, accountability, and audit of the national budget performance statement. This system improves management of the financial system in the area of resource consumption and national budget through a continuous financial control and supervision of the public resources consumption. The lack of timely and quick access to information and audit data resulting from traditional implementation of affairs reduces the accuracy and quality of the audits in addition to increasing the cost and time. Accordingly, the Ministry of Economic Affairs and Finance launched an electronic surveillance system known as the "SANAMA" as one of the major IT-based developments in the country in order to resolve the problem mentioned above and also to change and update the audits. Data were collected using questionnaire method. Based on one-sample t-test, the respondents represented a consensus of opinion on three issues raised in this research including improvements in auditing, transparency, and accountability of financial statements in executive organizations as the consequences of SNAMA system usage.Keywords: Information technology (IT), SANAMA system, Transparency, Accountability, Audit.